The Dynamics of National Resilience Amidst Global Community Integration - Nashwa Linta Nayla Admaja; Lathifah Meilani (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2026)
The rapid progression of globalization has had a significant impact on various sectors of national life, ranging from ideology, politics, economics, socio-culture, to national security. While global openness creates opportunities for growth and expands international cooperation, it simultaneously introduces challenges that may disrupt a nation’s identity, stability, and sovereignty. This study aims to examine the dynamics of Indonesia’s national resilience amid the integration of global society through a literature review approach. Data were collected by analyzing books, scholarly articles, journals, and other relevant documents related to national resilience and contemporary global threats. The findings indicate that national resilience is often influenced by non-traditional threats such as cyberattacks, misinformation, digital radicalism, and the infiltration of foreign cultures that may weaken national identity. Therefore, strengthening national character, improving digital literacy, enhancing cybersecurity, and ensuring political stability are strategic efforts to build adaptive national resilience. This study also emphasizes the importance of collaboration between the government, society, educational institutions, and the private sector to achieve comprehensive and sustainable national resilience.